Analysis of the Implementation of Good Governance in Village Fund Management (Case Study of Niur Permai Village, Sugie Besar District, Karimun Regency) - Herlina; Alfiandri; Okky Rizki Azizi (Darul Yasin Al Sys, 2026)
Good governance emphasizes transparency, accountability, participation, responsiveness, and effectiveness in public administration to promote responsible governance, improve public service delivery, and advance community welfare. This study examines the implementation of good governance principles in Village Fund management in Niur Permai Village, Sugie Besar District, Karimun Regency. A qualitative descriptive approach was employed, with data collected through observation, interviews, and documentation. Data were analyzed using the Miles, Huberman, and Saldana model, comprising data condensation, data display, and conclusion drawing and verification. The findings indicate that good governance principles have been implemented relatively well in Village Fund management. Transparency is demonstrated through the dissemination of information concerning Village Fund administration, while accountability is reflected in financial reporting and responsibility mechanisms that comply with applicable provisions. Community participation occurs primarily through village deliberation forums that facilitate the expression of public aspirations. The village government has also demonstrated responsiveness by addressing community needs and following up on public input, although this aspect requires further improvement. Moreover, the effective allocation of Village Funds has supported development and community empowerment programs in accordance with established targets. Nevertheless, implementation remains constrained by the limited capacity of village officials, dynamic regulatory changes, and adjustments to budget priorities. The study concludes that strengthening the capacity of village officials, expanding meaningful community participation, and optimizing good governance practices are essential to achieving more transparent, accountable, participatory, responsive, and effective Village Fund management. These findings provide practical implications for improving village-level financial governance and strengthening the quality of local public administration.